Perkembangan Sistem Informasi Manajemen (SIM) Di Indonesia - Rizky Khaliq; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
A management information system is a logical system that provides all information to assist the operational, management and decision-making functions of an organization. A management information system (MIS) is an information system that can create output results using inputs and various processes needed to achieve certain goals in a management matter. This type of research uses a qualitative method, where qualitative is a type of research method that uses a descriptive approach because this research can describe how Management Information Systems (MIS) can develop and advance in Indonesia. The development of management information systems has caused quite significant changes to the decision-making patterns carried out by management both at the operational level and (technical implementers) as well as leaders at all levels.